Bridging The Publication Gap Through A Mentor–Mentee Program in Islamic Higher Education - Muhammad Ali Gunawan; Minati Maulida; Amalia Fitri (Communautaire: Journal of Community Service, 2025)
Publication performance remains a significant challenge in private Islamic universities, where limited academic guidance and inadequate writing support hinder faculty members' scholarly productivity. This community service program was designed to bridge the publication gap by implementing a structured Mentor-Mentee model targeting early-career faculty members in Islamic religious colleges—the three-month intervention integrated diagnostic assessments, intensive writing workshops, individual mentoring, and simulated peer review. A mixed-methods approach was used to evaluate the program's effectiveness, combining rubric-based pre- and post-writing assessments with qualitative reflection and submission tracking. Findings demonstrated substantial improvements in manuscript structure, referencing accuracy, and methodological clarity. By the end of the program, half of the participants had produced full-length manuscripts, and more than half had submitted them to nationally accredited journals. Feedback revealed increased confidence and a stronger scholarly identity among the mentees. This initiative not only improved technical writing skills but also fostered a collaborative academic culture within the institution. The Mentor-Mentee model has proven effective in addressing systemic barriers to publication and offers a scalable solution for other under-resourced Islamic universities seeking to build sustainable research capacity. Its successful implementation contributes to broader efforts in strengthening academic output and institutional accreditation in the Indonesian higher education context.